Hemodynamic modeling of aortic arch aneurysm treatment using the Castor™ branched stent graft: a virtual coil embolization simulation framework - Ye, Xiaoqiang; Zhang, Jianning; Cheng, Zhiguo; Lu, Fenghui; Wen, Zijing; Yu, Guanghao; Chen, Guangxin; Xie, Fengjie; Qiao, Dan; Xing, Jian; Tan, Wenchang; Zhao, Dongliang; et al. (Frontiers in Physiology, 2025)
IntroductionAortic arch aneurysm (AAA) refers to pathological dilation of the aortic arch, carrying high rupture risks under hypertensive conditions with critical mortality rates, thus remaining a key research focus. The Castor™ single-branched stent-graft effectively isolates the aneurysm from circulatory pressure and is clinically combined with coil embolization to enhance therapeutic outcomes. However, comprehensive hemodynamic analyses evaluating the therapeutic efficacy of this combined approach remain lacking. MethodsThis study establishes the first patient-specific hemodynamic model for Castor™ stent-graft-treated AAA, investigating pre- and postoperative biomechanical changes. A novel virtual coil embolization simulation methodology was developed to analyze the effects of coil length and morphology on aneurysmal hemodynamics. Results and discussionResults demonstrate significant aneurysmal pressure attenuation post-stent implantation, complete endoleak prevention, and enhanced proximal left common carotid (LCC) flow, while coil embolization induces localized hemodynamic alterations without perturbing major branch outflow. Progressive coil lengthening and packing density elevation correlate with expanded low-TAWSS regions and elevated OSI/RRT values, mechanistically confirming thrombosis acceleration. Systematic evaluation reveals synergistic hemodynamic interplay between stent-graft-mediated macroscale flow reconstruction and coil-induced thrombogenic microenvironments, providing critical insights for personalized AAA management.